ORIGINAL LOCAL GOVERNMENT REVENUE INFLUENCED BY THE NUMBER OF TOURISTS, HOTELS, AND RESTAURANTS IN PROVINCE OF CENTRAL KALIMANTAN - Hilmi Satria Himawan (State Islamic Institute (IAIN) Tulungagung, 2022)
This study aims to discover effect of the number of tourists, restaurants, and hotels on original local government revenue in Central Kalimantan. Research data using secondary data from publication of Direktorat Jendral Perimbangan Keuangan. The population is all of districts and town in Central Kalimantan. Author determines sample using purposive sampling technique. There are 11 sample (10 districts and 1 town) in the last 6 years. Data analyzed using multiple regression. The result show: 1) number of tourists has a positive and significant effect on original local government revenue in Central Kalimantan 2) number of restaurants has a positive and significant effect on original local government revenue in Central Kalimantan 3) number of hotels has a positive and significant effect on original local government revenue in Central Kalimantan 4) number of tourists, restaurants, and hotels has a positive and significant effect on original local government revenue in Central Kalimantan.